2022
DOI: 10.1002/adom.202102287
|View full text |Cite
|
Sign up to set email alerts
|

How to Obtain Anti‐Thermal‐Quenching Inorganic Luminescent Materials for Light‐Emitting Diode Applications

Abstract: phosphor-converted light-emitting diodes (pc-LEDs) have been widely used in solidstate lighting, backlighting, near-infrared (NIR) light sources, etc. [1] As an important component in pc-LED devices, phosphors have been developed rapidly because of their attractive and tunable optical properties. Photoluminescence (PL) thermal stability of phosphor materials is evaluated by the thermal quenching (TQ) behavior, which is related to the electronic/crystal structure, structural rigidity, and chemical composition … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
74
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 113 publications
(78 citation statements)
references
References 124 publications
0
74
0
Order By: Relevance
“…This antithermal-quenching behavior is very rare in Bi 3+ -activated phosphors. It has been reported that the generation of oxygen vacancies may lead to traps, which can capture and store electrons and photons. , When at high temperature, the electrons and photons would release from traps to compensate for the energy lost in thermal quenching, resulting in an antithermal-quenching behavior . EPR analysis of the La 3 SbO 7 :0.03Bi 3+ and LaGd 2.0 SbO 7 :0.03Bi 3+ phosphors were measured to verify the existence of oxygen vacancies.…”
Section: Resultsmentioning
confidence: 99%
“…This antithermal-quenching behavior is very rare in Bi 3+ -activated phosphors. It has been reported that the generation of oxygen vacancies may lead to traps, which can capture and store electrons and photons. , When at high temperature, the electrons and photons would release from traps to compensate for the energy lost in thermal quenching, resulting in an antithermal-quenching behavior . EPR analysis of the La 3 SbO 7 :0.03Bi 3+ and LaGd 2.0 SbO 7 :0.03Bi 3+ phosphors were measured to verify the existence of oxygen vacancies.…”
Section: Resultsmentioning
confidence: 99%
“…This may be due to the non-equivalent substitution of Cr 3+ for Mg 2+ in the MAS matrix where there are oxygen vacancy defects, which contribute to enhancing the process of non-radiative transitions, resulting in the luminous intensity of MAS:Cr at 398 K being only 45.2% of that at 298 K. The thermal stability can subsequently be improved utilizing charge compensation. 52…”
Section: Paper Dalton Transactionsmentioning
confidence: 99%
“…Zhiguo Xia et al 34 enhanced the non-radiative relaxation of Cr 3+ by increasing the structural rigidity and local symmetry through Al/Sc substitution, thus suppressing it. Peipei Dang et al 35 reported that the review was done by seven different strategies to obtain phosphors with anti-thermal-quenching performance. However, the aforementioned studies are limited to specific substrates and structures which are not common, so it is difficult to generalize their tactics.…”
Section: Introductionmentioning
confidence: 99%